Effects of Mesenchymal Stem Cell-conditioned Media with Natural Immunomodulatory Agent Resveratrol on Type 1 Diabetes - Abhale, Krushna; Addepalli, Veeranjaneyulu; Desai, Shivani; Sanap, Avinash; Bhonde, Ramesh (Current Drug Discovery Technologies, 2025)
Background Type 1 diabetes mellitus (T1DM) is a condition marked by elevated blood sugar levels and primarily recognized by the destruction of beta cells caused by an autoimmune attack, which is a significant characteristic of T1DM. Recent studies have demonstrated the regenerative potential of conditioned medium therapy. In light of this, the current research sought to assess the impact of Mesenchymal Stem Cell conditioned media (CM) and CM with resveratrol (CM+ Resveratrol) on the management of T1DM in Swiss albino mice. By leveraging and modifying existing conditioned medium therapy, this study aims to evaluate its effectiveness in treating T1DM. Materials & Methods Diabetes was induced in animals using the diabetes-inducing agent streptozotocin (STZ). The animals were then divided into five groups: Normal control, Disease Control, Resveratrol, Condition Media, and CM + Resveratrol. Treatments were given to the animals accordingly. The study period was 28 days. During this time, the animals were monitored for food-water intake twice a week, blood glucose levels, and body weight. At the conclusion of the 28-day study period, biochemical estimations were performed for serum insulin levels, C-peptide levels, anti-inflammatory cytokines levels and pro-inflammatory cytokines levels. Additionally, histopathology of the pancreas was performed. Results The test groups showed a significant decrease in blood glucose levels, an increase in C-peptide levels, and a decrease in pro-inflammatory cytokine levels compared to the disease group. However, no statistically significant change within groups was observed in terms of serum insulin and anti-inflammatory cytokine levels. The improvement in diabetic symptoms, such as polyphagia, polydipsia, and weight loss, was observed in the treatment group, along with pancreatic regeneration, which indicated improved insulin secretion. Conclusion In the current investigation, we concluded that CM and CM+ Resveratrol, as natural immunomodulators, have the capacity to regenerate injured pancreatic beta cells and have antidiabetic action, together with immunomodulating impact. Nonetheless, future studies on this therapy appear to be promising.
Keywords: pancreatic beta cells